Ta‘limda fanlararo integratsiyani ta‘minlashda innovatsion ta‘lim texnologiyalardan foydalanish (SCIENCE and SOCIETY, 2023)
This article presents the effectiveness of the teaching methodology using innovative educational technologies in providing interdisciplinary integration of education.